A facile approach to construct organic D–π–A dyes via sequential condensation reactions for dye-sensitized solar cells. Issue 1 (26th November 2020) - Chen, Hongjin; Islam, Ashraful; Chowdhury, Towhid H.; Bedja, Idriss; Ghaithan, Hamid M.; Zhang, Rui; Liu, Jian
Abstract : We developed a facile strategy to construct organic D–π–A dyes via sequential condensation reactions for dye-sensitized solar cells. Abstract : We developed a new strategy for the molecular engineering of organic D–π–A sensitizers for dye-sensitized solar cell (DSSC) applications. Different from the synthesis of organic D–π–A dyes by conventional C–C coupling method, the present approach highlights the construction of D–π–A backbone via sequential condensation reactions. This approach avoids noble metal catalysis as well as harsh reaction conditions. Based on this concept, four organic D–π–A dyes have been developed as sensitizers for DSSCs, which produced high IPCE values and photovoltage. Moreover, expansion of the π-conjugated spacer in this type of dyes resulted in enhanced photovoltaic performance, which provided a new pathway for designing D–π–A dyes.